Influenza A viruses dual and multiple infections with other respiratory viruses and risk of hospitalisation and mortality. Issue 6 (19th October 2012) - Goka, Edward; Vallely, Pamela; Mutton, Kenneth; Klapper, Paul
<x xml:space="preserve">Abstract</x> Please cite this paper as: Goka et al. (2013) Influenza A viruses dual and multiple infections with other respiratory viruses and risk of hospitalisation and mortality. Influenza and Other Respiratory Viruses 7(6), 1079–1087. Introduction Recent literature suggests that dual or multiple virus infections may affect disease severity. However, few studies have investigated the effect of co‐infection with influenza A viruses. Objectives To identify the association between influenza A and respiratory viruses co‐infections with disease outcome. Methodology Data for samples from North West England tested between January 2007 and June 2011 was analysed for patterns of co‐infection between influenza A viruses and eight respiratory viruses. Risk of hospitalisation to ICU or general ward in single versus co‐infections was assessed using logistic regression. Results Of the 25 596 samples analysed for respiratory viruses 40·7% (10 501) were positive for any virus. Co‐infections were detected in 4·7% (137/2879) of all patients with influenza A(H1N1)pdm09, and 7·3% (57/779) of those with other influenza A virus infections. Co‐infection between seasonal influenza A viruses and influenza B virus was associated with a significant increase in the risk of admission to ICU/death (OR: 22·0, 95% CI: 2·21–219·8, P = 0·008). Respiratory syncytial virus/influenza A (RSV/Flu A) co‐infection also increased this risk but was not statistically significant. For influenza A(H1N1)pdm09, RSV and AdV co‐infection increased risk of hospitalisation to general ward whereas Flu B increased risk of admission to ICU, but none of these were statistically significant. Conclusion Co‐infection is a significant predictor of disease outcome; combined treatment, introduction of an integrated vaccine for all respiratory viruses and development of multi‐target rapid diagnostic tests is recommended. Integration of respiratory viruses' co‐infections into public health reports could also contribute to the accumulation of evidence.